Aufstieg und Niedergang des Schulklassizismus in Russland im 19. Jh. - Pozdnev, Michael (Hyperboreus, 2016)
In analyzing the didactic aspects of D. A. Tolstoy’s educational reform and the shortcomings of the classical system introduced by him in 1871 I emphasize the difference between two educational models based on the study of classical languages, one focused on understanding of the ancient texts and the other aimed at the assimilation of the intellectual values of Greeks and Romans, their “Weltanschauung”. The latter form presented in the learned schools of Prussia was fostered by the neohumanistic ideology of W. von Humboldt and his like-minded collaborators and followers. The ﬁrst type was more or less successfully practiced in Russian gymnasiums since the beginning of S. S. Uvarov’s ministerial career. After D. Karakosov’s assassination attempt against Alexander II the educational policy was provided with new guidelines. Thus Tolstoy was forced to introduce the “hard” grammatical model (including extemporalia as the principal element). Its obligatory character together with the limitations on educational opportunities turned to be fatal for the school classicism causing hatred against the government and sympathy for weak students. This was at the bottom of the crisis of 1899–1901 and resulted in the actual abandonment of the classical system in 1903.